Modern clinic design : strategies for an era of change - Vickery, Christine Guzzo; Nyberg, Gary; Whiteaker, Douglas (Wiley, 2015)
Shift Clinic design to keep pace with the evolving healthcare industry Modern Clinic Design: Strategies for an Era of Change is a comprehensive guide to optimizing patient experience through the design of the built environment. Written by a team of veteran healthcare interior designers, architects, and engineers, this book addresses the impacts of evolving legislation, changing technologies, and emerging nontraditional clinic models on clinic design, and illustrates effective design strategies for any type of clinic. Readers will find innovative ideas about lean design, design for flexibility.